The role of mechanics in elongate fish swimming behavior: Comparative studies of the vertebrae, skin, and body in sixteen species of fishes - Donatelli, Cassandra. (Tufts University. Tisch Library., 2019)
Fish are the largest and most diverse group of vertebrates, with a wide array of body shapes and behaviors. Certain body shapes and behaviors have long been hypothesized to confer high performance, but these hypotheses have rarely been tested. In principle, the diversity of fishes would make multi-species studies of characters easy, but, since characters tend to co-vary, it is difficult to determine how any specific character affects a specific behavior. Researchers have therefore resorted to studying small subsets of the population or computational or physical models. Although the extreme diversity is challenging, in my dissertation, I combined studies of computational and physical modeling, morphology, and mechanics to make larger conclusions about fish behavior. For example, I studied six species of elongate fishes and quantified how much their bodies twist, or "wobble", during swimming. I found that the amplitude of this twisting wave varied down the length of the body among fishes from different habitats. If wobble was a passive effect, I would expect it to relate to the passive torsional stiffness of the fishes' bodies. However, when comparing wobble to torsional stiffness there was no correlation, which lead me to further hypothesize that it was either related to another morphological feature, or actively controlled during swimming. The fish could benefit from active control as these species are negatively buoyant and have a small or non-existent swim bladder. The torsional wave might help to direct lateral forces downwards to help lift them off the bottom. Since the overall torsional mechanics of the body was not related to wobble, I then hypothesized it might be more related to the mechanical properties of specific parts of the body such as the vertebral column or skin. I first measured vertebral morphology in sixteen species of fishes and created a statistical model that describes how mechanics and kinematics can be predicted from morphology. Though there was no single relationship among all sixteen species, I was able to create significant models when I divided fish up into intertidal, nearshore, and subtidal habitats. Then, looked at the structure of the skin. Fish skin is composed of a fatty matrix with embedded collagen fibers that are organized in helices around the body. I measured the angle of these fibers in the same six species of elongate fish as in the first study and examined the relationship between their angle, and the wobble kinematics and torsional stiffness of the fishes. I also made passive models and tested the effect of fiber angle on bending stiffness. Like the previous results, I found that the relationship between fiber angle and wobble differed for different habitat groups. These studies show the power of combining comparative studies of multiple species and their different behaviors with physical models when investigating the role of morphology on mechanics, kinematics, and behavior.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Biology.; Advisor: Eric Tytell.; Committee: Barry Trimmer, Elizabeth Crone, and Adam Summers.; Keyword: Biomechanics.